1994
DOI: 10.1029/94jd00318
|View full text |Cite
|
Sign up to set email alerts
|

Observations of lightning phenomena using radio interferometry

Abstract: A radio interferometer system is described which utilizes multiple baselines to determine the direction of lightning radiation sources with an angular resolution of a few degrees and with microsecond time resolution. An interactive graphics analysis procedure is used to remove fringe ambiguities from the data and to reveal the structure and development of lightning discharges inside the storm. Radiation source directions and electric field waveforms have been analyzed for different types of breakdown events fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
133
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(159 citation statements)
references
References 19 publications
18
133
2
Order By: Relevance
“…Their observation is based on VHF/interferometric technique. This horizontal propagation of one or several discharge channels, before that or one of them diverting vertically towards ground, has clearly been observed in several other studies conducted in the same geographical location (e.g., 4 flashes in [22] and 2 flashes in [21]). Using radio interferometric technique, Hayenga and Warwick [31] have observed that the intracloud part of the lightning leaders is predominantly horizontal.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Their observation is based on VHF/interferometric technique. This horizontal propagation of one or several discharge channels, before that or one of them diverting vertically towards ground, has clearly been observed in several other studies conducted in the same geographical location (e.g., 4 flashes in [22] and 2 flashes in [21]). Using radio interferometric technique, Hayenga and Warwick [31] have observed that the intracloud part of the lightning leaders is predominantly horizontal.…”
Section: Introductionsupporting
confidence: 68%
“…One of them is VHF mapping, in which the RF radiation emitted by cloud electric activities are observed to employ time-of-arrival or interferometric techniques, to locate the regions of activity [16][17][18][19][20][21][22][23][24]. The oldest, yet, widely applied method is to obtain slow field variations at several measuring stations at ground, underneath the thunder cloud to locate the charge sources [9,11,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Most if not all small +IC flashes (<5 km) exhibit successions of short negative leaders from the origin as in the first 100 ms of this example, with few recoil sources. [Rhodes et al, 1994] which travel here in previous negative leader segments. Remarkable is also the appearance of a second positive/recoil trace, during which a negative leader reaches ground producing a ÀCG stroke (indicated by a black square marker) near the flash origin (in this case the reference for distance and t = 0 is the ÀCG location and time).…”
Section: Examples Of Simple Intracloud Flashes (+Ic)mentioning
confidence: 97%
“…Structures in the radio emission of this lightning are very nicely resolved in all 30 antennas. (Rhodes et al, 1994). For example the lightning strike displayed in Fig.…”
Section: Radio Signal From Lightning Strikesmentioning
confidence: 99%